Literature Review: Model Discovery Learning pada Pembelajaran Pendidikan Jasmani di Sekolah Menengah Atas - Shela Ginanjar; Dena Widyawan; Eko Prabowo (Jurnal Pendidikan Olah Raga, 2022)
This study aims to determine and describe the effect of the Discovery Learning model on physical education in high school by looking at the achievement of physical education learning objectives. The method used Systematic Literature Review, the results found a 200 journals from 2012 to 2022 which were selected gradually and systematically into 9 journals relevant to the research topic. The results of the study indicated that the Discovery Learning model in physical education in high schools has a positive outcomes for the students, this result can proven from the achievement of the objectives of learning physical education in high schools that have been set by the government in this case is Kementerian Pendidikan dan Kebudayaan Republik Indonesia.